Performance Evaluation of Rotating Cylinder Type Coffee Bean Roaster - Sutarsi .; Siswoyo Soekarno; Sukrisno Widyotomo (PERTETA, 2010)
Abstract One strategy attempts to reduce dependence on primary commodity markets are overseas market expansion and development of secondary products. In the secondary product processing coffee beans is required of supporting equipment to facilitate these efforts. Research Center for Indonesian Coffee and Cocoa has developed coffee bean roaster. However, there are still many people who do not know about the technical aspects of roaster machine type of rotating cylinder so that more people use traditional ways to roast coffee beans. In order for the benefits of this machine is better known society it is necessary to study on the technical aspects. The purpose of this research is to evaluate the technical performance of the coffee beans roaster machine type of rotating cylinder. These include the technical aspects of work capacity of the machine, roasting technical efficiency, fuel requirements, and power requirements of using roaster machine. Research methods are including data collection, calculation and analysis. The results showed that the roaster machine type of a rotating cylinder has capacity of 12.3 kg/hour. Roasting efficiency is 80%. Fuel consumption is 0.6 kg. The calculated amount of the used power of current measurement is the average of 0.616 kW. Keywords: coffee beans, roasting, performance Diterima: 21 Oktober 2009; Disetujui: 8 Januari 2010